Polyphenol-rich extract of Ocimum gratissimum leaves prevented toxic effects of cyclophosphamide on the kidney function of Wistar rats - Quadri K. Alabi; Rufus O. Akomolafe; Joseph G. Omole; Ayodeji Aturamu; Mokolade S. Ige; Oyindasola O. Kayode; Deborah Kajewole-Alabi (BMC, 2021)
Abstract Background Cyclophosphamide (CP) is one of the potent and low cost chemotherapy used in clinical setting against a variety of tumors. However, its association with nephrotoxicity limits its therapeutic use. Ocimum gratissimum leaf is a medicinal plant with numerous pharmacological and therapeutic efficacies, such as antioxidant, anti-inflammation, and anti-apoptotic properties. Methods The present study was designed to evaluate the protective effect of Ocimum gratissimum (OG) against CP-induced kidney dysfunction in rats. Rats were pre-treated with 400 mg/kg b.w. of leave extract of Ocimum gratissimum (Ocimum G.) for 4 days and then 50 mg/kg b.w. of CP was co-administered from day 5 to day 7 along with Ocimum G. Markers of renal function and oxidative stress, food and water intake, electrolytes, aldosterone, leukocytes infiltration, inflammation and histopathological alteration were evaluated. Results Obvious renal inflammation and kidney injuries were observed in CP treated groups. However, administration of leave extract of Ocimum G. prevented oxidative stress, kidney injuries, attenuated inflammation, increased aldosterone production and reduced sodium ion and water loss in rats. The plasma creatinine, urea and urine albumin concentration were normalized after the administration of Ocimum G. extract in rats treated with CP. Ocimum G. also decreased the plasma concentrations of Interleukin-(IL)-6, C-reactive protein and activity of myeloperoxidase and malondialdehyde in CP treated rats. Conclusion Ocimum G. prevented kidney injury and enhanced renal function via inhibiting inflammation and oxidant-induced CP toxicity. The efficacy of Ocimum G. is related to the presence of various phytochemicals in the plant.